Model Sensitivitas Kenaikan Tarif Dasar Listrik Terhadap Keberlangsungan Usaha UMKM Di Kota Bandung - Vita Sarasi; Ina Primiana; Umi Kaltum; Merita Bernik (Operations Excellence: Journal of Applied Industrial Engineering, 2021)
Micro Small and Medium Enterprises (MSMEs) are often faced with a number of problems that are very influential on their growth and can reduce their competitiveness, where one of them is the increase in Basic Electricity Tariff. The increase in Basic Electricity Tariff will occur every three months and the average annual increase is 15%, which will result a direct impact on surging production costs. The increase in Basic Electricity Tariff will result in declining growth of MSMEs, making it difficult to compete because MSMEs have to make adjustments to prices and ultimately result in weakening purchasing power. The Sensitivity Analysis of Basic Electricity Tariff increase on the sustainability of MSME businesses aims to (1) Know the structure of production costs in relation to electricity usage and (2) Create a sensitivity model for TDL increase on the sustainability of MSME businesses using Data Envelopment Analysis (DEA). This research is analytical descriptive and useful as an effort to focus on actions in anticipating the sensitive increase in Basic Electricity Tariff on the sustainability of MSME businesses. These actions include reducing the ratio of electricity costs to production costs and increasing capital to increase business turnover. This research is focused on MSMEs which are very sensitive to the increase in the Basic Electricity Tariff.